NEGATIVE FACTORS AND ITS EFFECT TOWARDS JOB SATISFACTION OF NURSES - Desti Ranihusna; Nury Ariani Wulansari; Dikha Karuma Asiari; Reza Enindra Syahputra (Jurnal Manajemen dan Pemasaran Jasa, 2019)
The primary function of nurses in inpatient services is to provide optimal services for patients with serious illnesses.Therefore, nurses’ job satisfaction should not be taken for granted. The role overload can influence job satisfaction at workplaces. The role overloaand job stress have negative effect. However, the nurses can still have job satisfaction, if the role overload is at low level. The other factor that influences job satisfaction is role ambiguity. The aim of this study is to analyze the factors that determine job satisfaction of nurses, work at the hospital and the job stress impacts on job satisfaction. The samples of this study were 170 respondents. This study applied quantitative design with path analysis. The role overload and job stress have negative and significant influence on job satisfaction. The role overload and role ambiguity have a positive and significant impact on job stress. The role ambiguity does not influence job satisfaction. Job stress mediates the role ambiguity to job satisfaction. The next research can develop variables that can mediate the influence of role ambiguity and role conflict on job satisfaction, for example, burnout and performance variables.